Thinned young apple polyphenols may prevent neuronal apoptosis by up-regulating 5-hydroxymethylcytosine in the cerebral cortex of high-fat diet-induced diabetic mice. Issue 7 (17th March 2023) - Ma, Qingqing; Gao, Jing; Fan, Qiang; Yang, Tao; Zhao, Zhuang; Zhang, Shuangxi; Hu, Ranrui; Cui, Li; Liang, Bing; Xie, Xiuying; Liu, Jiankang; Long, Jiangang
Abstract : TYAPs maintain the TCA cycle and mitochondrial homeostasis to activate TET2 in the cerebral cortex. TYAPs improve diabetes-induced neuronal apoptosis through restoring the 5hmC level, which is mediated by the up-regulation and activation of TET2. Abstract : Apple polyphenols exert neuroprotective effects by improving the mitochondrial tricarboxylic acid (TCA) cycle function, but the details of their mechanisms are still not fully understood. TCA cycle metabolites regulate the level of 5-hydroxymethylcytosine (5hmC) by affecting the ten-eleven translocation (TET) enzyme activity. Therefore, we hypothesized that thinned young apple polyphenols (TYAPs) inhibit neuronal apoptosis by up-regulating the level of 5hmC in the cerebral cortex of high-fat diet-induced diabetic mice. C57BL/6J mice were randomly divided into 5 groups ( n = 10 each group): the control (CON) group, the high-fat diet (HFD, negative control) group, the lovastatin (LOV, positive drug control) group, the resveratrol (RES, positive polyphenol control) group and the TYAP group during an eight-week intervention. The presented results verified that in the HFD group, the level of 5hmC and the expression of TET2 in the cerebral cortex were significantly lower, and the ratio of (succinic acid + fumaric acid)/α-ketoglutarate and the neuronal apoptosis rate were significantly higher than those in the CON group. However, TYAP intervention effectively restored the level of 5hmC through up-regulating the expression and activity of TET2, so as to improve diabetes symptoms and prevent diabetes-induced neuronal apoptosis.